SIMULASI UJIAN TRY OUT UTBK-SBMPTN ONLINE MELALUI PLATFORM WEB BASED LEARNING BAGI SISWA-SISWI KELAS XII DI SMA N KOTA CIREBON - Sulaiman, Herri; Khaerudin, Iyay Robia (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
Every year the students of class XII SMA/SMK/MA compete to register themselves to enter PTN through the UTBK SBMPTN route. However, the situation is different for 2021 at this time, where the Covid 19 pandemic condition that hit Indonesia changed the exam system that had been implemented so far from offline to online. Schools are competing to guide and direct class XII students to take part in the UTBK SBMPTN. However, schools face obstacles because during the current Covid-19 Pandemic, teaching and learning activities at schools are stopped and students study online at home. This is a problem for which schools, they do not have their own LMS or web learning system to simulate the Try Out UTBK SBMPTN Online. This opportunity is used as material for the PKM team in carrying out community service activities by creating a special web learning system for the preparation of the UTBK SBMPTN Online through the online UTBK SBMPTN Try Out simulation link that has been designed. The purpose of the PKM activity is to introduce the UTBK SBMPTN Online Try Out simulation link to teachers and school principals at SMA N Cirebon City so that they have their own web learning system and can carry out independent Try Outs in the coming years. Meanwhile, for class XII students, it can be used as a training ground to know their own abilities and increase their readiness and preparation in facing the UTBK SBMPTN Online in April 2021.